(Nota n.º 2) Fixação do dióxido de carbono e fosforilação em Nitrobacter agilis - Malavolta, E.; Delwiche, C. C.; Burge, W. D. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
1. Intact cells of Nitrobacter agilis fix CO2 during the oxidation of nitrite according to the same pathway found to occur in photosynthesis by higher plants. Activity of carboxidismutase - the crucial enzyme for fixation - was demonstrated in cell free extracts. 2. High energy phosphates (as ATP) are generated during the oxidation of nitrite with an apparent P/O ratio of 0.5.